Functional characterization of macrophage receptors for in vitro phagocytosis of unopsonized Pseudomonas aeruginosa. - Speert, D P (1988)
The phagocytic receptor for unopsonized Pseudomonas aeruginosa was characterized functionally using human monocyte-derived macrophages. Freshly isolated human peripheral blood monocytes were unable to ingest unopsonized P. aeruginosa; ingestion did not occur until the cells had been in culture for 2 d and it became maximal after 4 d. Macrophages plated on coverslips derivatized with anti-BSA IgG or with human gamma-globulin lost the capacity to phagocytose unopsonized P. aeruginosa, unopsonized zymosan, and EIgG but bound C3bi-coated erythrocytes normally. Each of the four human IgG subclasses and Fc fragments of anti-BSA IgG inhibited phagocytosis of both unopsonized P. aeruginosa and EIgG. Phagocytosis of P. aeruginosa and zymosan was markedly impaired and EIgG minimally inhibited if macrophages were plated on coverslips derivatized with mannan or when mannan was added to the phagocytosis buffer. Phagocytosis of P. aeruginosa and zymosan, and binding of EC3bi was dependent on the presence of divalent cations, but phagocytosis of EIgG was not. The macrophage phagocytic receptor for unopsonized P. aeruginosa was inactivated by proteolytic enzymes. Phagocytosis of P. aeruginosa was inhibited by D-mannose, L-fucose, and alpha methyl mannoside, but not by L-mannose, D-fucose, or D-glucose. The same sugars inhibited phagocytosis of unopsonized zymosan. We conclude that phagocytosis of unopsonized P. aeruginosa by human monocyte-derived macrophages is facilitated by mannose receptors.